Tingkat Kenyamanan Taman Balai Kota Bandung Berdasarkan Perspektif Pengunjung - Rivaldo Manurung; Grandy Loranessa Wungo (Jurusan Perencanaan Wilayah dan Kota, 2023)
Park is a public space that accommodates the activities of the community, both individuals and communities. Bandung City Hall Park is one of the public spaces in the city of Bandung which has a strategic location. In 2017 the park was still of low quality, then after improvements to the facilities were made and it was inaugurated, the park was getting more and more crowded. However, in the last two years, visitors have provided reviews stating that they are not satisfied with the current condition of the city hall park which certainly affects the comfort of visitors. This study focuses on analyzing the comfort level of Bandung City Hall Park based on the perspective of its visitors. The method used is scoring and descriptive quantitative, while the sampling technique used is simple random sampling. Based on the analysis, it was found that the current level of comfort at the Bandung City Hall Park is 77.67 or is in a good interval. Visitors feel that accessibility, climate comfort, walking comfort, and cleanliness convenience are good. However, there are several things that need to be improved again, namely a sense of security with the addition of lighting and CCTV, seating comfort with additional chairs and seat adjustment according to standards.